Objective neurophysiological measures of cognitive performance in elite ice hockey players - Kirby, E. D.; Jones, K.; Campbell, N.; Fickling, S. D.; D'Arcy, R. C. N. (Open Access Journal of Sports Medicine, 2025)
Introduction: Athletic peak performance is increasingly focused on cognitive and mental factors. In the current study, cognitive performance was measured by neurophysiological responses in elite Junior-A hockey players.